Contestação do sistema eleitoral e seu impacto na confiança das eleições presidenciais: uma análise agregada e multivariada das últimas séries históricas (2006–2023) - Passos, Mateus Costa (2025)
The attempted disruption of Brazil’s democratic regime on January 8, 2023, seems to indicate that the increase in distrust in the electoral system has impacted Brazilian voters. Recognizing the importance of this phenomenon, scholarly literature has focused on understanding the rise and behavior of populist and authoritarian political leaders – particularly in Europe, with Brexit, and in the United States, with Donald Trump – who have challenged democratic norms. Based on this theoretical foundation, this paper seeks to contribute by proposing the following research question: What is the impact of Jair Bolsonaro's rhetoric, which is antagonistic toward the Brazilian electoral system, on confidence in presidential elections, especially from 2018 to 2022? The hypothesis is that Jair Bolsonaro, the main representative of the Brazilian right during the period analyzed, has managed to influence public opinion – particularly among voters positioned further to the right on the ideological spectrum – by repeatedly alleging fraud in the 2018 and 2022 elections, diminishing their trust in the electoral system. To test this hypothesis, we analyze longitudinal data (2006 –2022) from the Barômetro das Américas, collected by the Latin American Public Opinion Project (LAPOP), Latinobarômetro, and data from the Estudo Eleitoral Brasileiro (ESEB). The justification for this work is based on the understanding that adherence to the rules of the democratic game is essential for regime consolidation. Based on this, we construct binomial logistic regression models to assess trust in the electoral system (dependent variable), using explanatory variables such as ideology, voting intention, gender, region, age and income bracket, and religion. The objective is to determine whether there is a trend among Brazilian voters toward increased distrust in electoral procedures in 2018 and 2022, driven by Jair Bolsonaro's rhetoric. The results show that: 1) the impact of Jair Bolsonaro's rhetoric on confidence in the presidential elections was statistically significant only in 2022, when he was already President of the Republic and his speeches were beginning to have institutional reach; 2) only voters who declared their vote for Jair Bolsonaro – in the first round of elections in 2018 and 2022 – elections exhibited lower levels of confidence in the electoral system, suggesting that the president's rhetoric did not have a statistically significant influence on other right-wing groups, such as those who expressed their intention to vote for Simone Tebet and Geraldo Alckmin; 3) A relevant finding concerns voters identified with the right and center ideological spectrums, who, throughout the historical series, trust the Brazilian electoral system more than those who identify with the left spectrum.